The additive inverse of a number x is a number y such that
![x+y=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1dhefr3q3wh6ogt7xub6hxofiji0pn1kdj.png)
From this definition, we can derive
![y=-x](https://img.qammunity.org/2020/formulas/mathematics/college/x46wwkea6gjvtlc04d66ywn4x3ngkq4lt2.png)
So, to get the additive inverse of a number, you simply have to switch its signs.
Since complex numbers are made of two pieces (real and complex parts), you'll have to switch both signs:
![z=-8+3i \implies -z = 8-3i](https://img.qammunity.org/2020/formulas/mathematics/middle-school/240jfjujjznbaxcr4exv7bzxr28e975xd6.png)
In fact, if you try to sum them, you have
![(-8+3i)+(8-3i)=(-8+8)+(3i-3i)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y8hb72a9679lzutvglyzdgzzd6ovey17lf.png)